Entanglement is a costly life‐history stage in large whales. Issue 1 (11th December 2016) - van der Hoop, Julie; Corkeron, Peter; Moore, Michael
Abstract: Individuals store energy to balance deficits in natural cycles; however, unnatural events can also lead to unbalanced energy budgets. Entanglement in fishing gear is one example of an unnatural but relatively common circumstance that imposes energetic demands of a similar order of magnitude and duration of life‐history events such as migration and pregnancy in large whales. We present two complementary bioenergetic approaches to estimate the energy associated with entanglement in North Atlantic right whales, and compare these estimates to the natural energetic life history of individual whales. Differences in measured blubber thicknesses and estimated blubber volumes between normal and entangled, emaciated whales indicate between 7.4 × 10 10  J and 1.2 × 10 11  J of energy are consumed during the course to death of a lethal entanglement. Increased thrust power requirements to overcome drag forces suggest that when entangled, whales require 3.95 × 10 9 to 4.08 × 10 10  J more energy to swim. Individuals who died from their entanglements performed significantly more work (energy expenditure × time) than those that survived; entanglement duration is therefore critical in determining whales' survival. Significant sublethal energetic impacts also occur, especially in reproductive females. Drag from fishing gear contributes up to 8% of the 4‐year female reproductive energy budget, delaying time of energetic equilibrium (to restore energy lost by a particular entanglement) for reproduction by months to years. In certain populations, chronic entanglement in fishing gear can be viewed as a costly unnatural life‐history stage, rather than a rare or short‐term incident. Abstract : In certain large whale populations, entanglement in fishing gear can be viewed as a costly unnatural life‐history stage, rather than a rare or short‐term incident. We present two bioenergetic approaches that suggest entangled large consume endogenous energy reserves on the same order of magnitude as during pregnancy, migration, and lactation which can impact calving intervals in these k‐strategist species.